Children applying Bhasma (sacred ash) - Mumbai Archive Project Team (Jio Institute, 2024)
Children apply bhasma (sacred ash) to their forehead, face, and arms. In Shaivism, bhasma (also known as vibhuti) reminds devotees of the transient nature of life, as it is a product of fire and symbolizes the ultimate reality of death and the dissolution of the physical body.